2019
DOI: 10.1177/1359105319888262
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating behaviours, body image and social networking in a type 1 diabetes population

Abstract: The purpose of this study was twofold: to examine predictors of disordered eating behaviours and body image dissatisfaction, including social networking, among type 1 diabetes population, and to qualitatively explore the relationship between type 1 diabetes management and body image. A convenience sample of 121 type 1 diabetes patients ( F = 106; Mage = 36 ± 6.5) was collected via online questionnaires, of which 98 patients responded to two open-ended questions. Young age and negative body image explained 58.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 33 publications
1
18
0
3
Order By: Relevance
“…Overall, the current findings corroborate the existing research on general and T1D populations supporting the association between body image problems and DEBs ( Colton et al, 1999 ; Striegel-Moore and Debra, 2002 ; Fairburn and Harrison, 2003 ; Striegel-Moore and Bulik, 2007 ; Kichler et al, 2008 ; Troncone et al, 2016 , 2018 ; Amaral and Ferreira, 2017 ; Falcão and Francisco, 2017 ; Girard et al, 2018 ; Verbist and Condon, 2019 ; Araia et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, the current findings corroborate the existing research on general and T1D populations supporting the association between body image problems and DEBs ( Colton et al, 1999 ; Striegel-Moore and Debra, 2002 ; Fairburn and Harrison, 2003 ; Striegel-Moore and Bulik, 2007 ; Kichler et al, 2008 ; Troncone et al, 2016 , 2018 ; Amaral and Ferreira, 2017 ; Falcão and Francisco, 2017 ; Girard et al, 2018 ; Verbist and Condon, 2019 ; Araia et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, empirical evidence has shown that in youths and adults with T1D, the level of satisfaction with their perceptions of body image (along with other factors such as BMI, global and physical appearance-based self-worth, and depression), weight, and shape were associated with higher levels of DEB ( Kichler et al, 2008 ; Troncone et al, 2016 , 2018 ; Verbist and Condon, 2019 ). Body image dissatisfaction was described to be a significant predictor of eating problems in adolescents and young adult participants with T1D ( Falcão and Francisco, 2017 ; Araia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In performing meta-analysis for the body dissatisfaction domain, we identified 24 studies in scope, four of which reported data separately for males and females. Pooled estimates are reported together (all studies; n = 15494) (Bair et al, 2012; Butkowski et al, 2019; Cohen and Blaszczynski, 2015; de Vries et al, 2019, 2016; Eckler et al, 2017; Hendrickse et al, 2017; Hummel and Smith, 2015; Levinson et al, 2017; McLean et al, 2015; Olenik-Shemesh and Heiman, 2017; Rodgers et al, 2020, 2019, 2013; Simpson and Mazzeo, 2017; Smith et al, 2013; Stronge et al, 2015; Tao, 2013; Terhoeven et al, 2020; Tiggemann and Miller, 2010; Veldhuis et al, 2018; Verbist and Condon, 2019; Xiaojing, 2017; Zeeni et al, 2018) and for males separately (Rodgers et al, 2020, 2019; Stronge et al, 2015; Xiaojing, 2017). The pooled estimate from all 24 studies was small, r = 0.16 (s.e.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, female sex and late adolescent/early adult age represent a high-risk period for the development of ED, which has also been supported among individuals with T1D (Colton et al, 2015). Reported correlates of ED psychopathology in adults with T1D include negative affect (Merwin et al, 2015; Moskovich et al, 2019), poorer executive functioning (Broadley et al, 2018), social media usage (Verbist and Condon, 2019), body image dissatisfaction (Verbist and Condon, 2019), depression (Olmsted et al, 2008), and anxiety (Bernstein et al, 2013). Psychological aspects such as coping strategies, insulin beliefs, and illness perceptions have been found to be associated with ED psychopathology among adolescent females with T1D, but not among adolescent males (Wisting et al, 2015).…”
Section: Introductionmentioning
confidence: 99%